2020
DOI: 10.1002/jper.20-0282
|View full text |Cite
|
Sign up to set email alerts
|

Elevated neutrophil‐to‐lymphocyte ratio but not platelet‐to‐lymphocyte ratio is associated with generalized aggressive periodontitis in a Chinese population

Abstract: Background Host inflammatory mediators are associated with tissue destruction in patients suffering from generalized aggressive periodontitis (GAgP). However, the correlations between neutrophil‐to‐lymphocyte ratio (NLR) and platelet‐to‐lymphocyte ratio (PLR) with GAgP remain unknown. Methods Periodontal clinical parameters, including probing depth (PD), bleeding index (BI) and attachment loss (AL) were collected from patients with GAgP and healthy controls. Complete blood cells analyses were obtained; further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 36 publications
2
24
0
Order By: Relevance
“…Serum levels of ferritin, NT-proBNP, neutrophil lymphocyte ratio and troponin have been found to be significantly associated with periodontal disease [36,38,39,41,42]. This association points towards a commonality between periodontal disease and COVID-19-related adverse outcomes.…”
Section: Discussionmentioning
confidence: 90%
“…Serum levels of ferritin, NT-proBNP, neutrophil lymphocyte ratio and troponin have been found to be significantly associated with periodontal disease [36,38,39,41,42]. This association points towards a commonality between periodontal disease and COVID-19-related adverse outcomes.…”
Section: Discussionmentioning
confidence: 90%
“…Regarding the selection section of the NOS scale, all the studies used pre-defined, transparent criteria to identify the presence of the disease (chronic periodontitis or aggressive periodontitis) and controls; thus, the case and control definitions were adequate. Nevertheless, the authors of the studies used different criteria to identify the disease according to official classifications (Periodontal Disease Classification, American Association of Periodontology 1999-three studies [ 23 , 25 , 28 ]; Classification of Periodontal and Peri-Implant Diseases and Conditions 2017-four studies [ 1 , 2 , 26 , 27 ]; Center of Disease Control and Prevention, American Academy of Periodontology Periodontal Disease Classification CDC/AAP-one study [ 29 ]), or no specified classification [ 7 , 24 ]. Only two studies (20%) out of ten had clear representativeness of the cases [ 23 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…For the other six, it might be difficult to assess if the selection of controls was correct. Half of the studies enrolled subjects from the department of periodontology [ 1 , 2 , 7 , 23 , 26 ]; the other studies enrolled subjects from the internal medicine [ 28 ] or cardiology departments [ 24 ], or from an electrical company [ 29 ], and in two studies, the population was not stated [ 25 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“… 44 In a more recent Chinese study, Lu et al reported that the NLR values, but not PLR, were positively correlated with the risk and clinical parameters of aggressive periodontitis, with the risk of aggressive periodontitis increasing by 20.6% for each 0.1 increase in NLR below NLR<3 values in their healthy control group, reaching saturation when NLR > 3. 45 Torrungruang et al 46 and Acharya et al, 33 on the other hand, reported that both high NLR and PLR indices were robustly linked to severity of chronic periodontitis. Although these studies are fundamentally different from the one presented here, they all indicate a strong link between severe tooth problems and the systemic immune/inflammation response, regardless of the disease type and therapy used.…”
Section: Discussionmentioning
confidence: 99%